The use of response surface methodology (RSM) to optimize the acid digestion parameters in fiber volume fraction test of aircraft composite structures - Hassan, M.H. (Springer London, 2017)
An acid digestion test has been widely used to determine the fiber volume fraction, Vf and void content of the PMCs laminate. Three main testing parameters of volume of acid, digestion period, and temperature were found to influence the resin extraction during the test. The study was aimed to establish the optimum values of those testing parameters through the use of statistical method of RSM. The exact values of each parameters was evaluated based on Vf, and hence, the percentage of difference in comparison to the target value. The results have indicated that the proposed mathematical model could adequately describe the performance indicators within the limits of the factors investigated. As per described via the model relationship, the optimum condition were established as 30 ml of sulfuric acid and 3.5–4 h of digestion period at 175 ± 5 °C. The error between the predicted and actual experiment values were between −1.52 and −2.43. © 2016, Springer-Verlag London.